Sorption of Natural Uranium on Weakly Basic Anion Exchangers. Issue 5 (29th July 2017) - Riegel, Marcel
ABSTRACT: The effects of the sorption of naturally occurring uranium on weakly basic anion exchangers (WBA) have been investigated. Systematic investigations on the effects of various parameters show in general three important factors influencing the adsorption equilibrium. First, the sorption depends on the presence of competing anions, with sulfates showing the greatest influence. Second, the speciation of uranium (VI), which in carbonate-containing waters in a pH range between 6.5 and 9 exists mainly as anionic complexes UO2 (CO3 )2 2- and UO2 (CO3 )3 4-, is changed by calcium and bicarbonates. Calcium forms neutral complexes with uranium and carbonate, and with these complexes no ion exchange occurs. On the other hand, increasing concentrations of carbonate species support the formation of anionic uranyl complexes of higher charge, and an increased uranium uptake arises. Third, the effective capacity of WBA depends on the pH. With increasing pH, the amount of protonated functional groups decreases and the sorption capacity decreases. It has been demonstrated that WBA sorb uranium very selectively out of drinking water. WBA Amberlite IRA 67 reached the uranium loading of 10 mg/g at the uranium concentration of 10 µg/L by sorption out of tap water at pH 7.